The Influence Of Adolescents' Knowledge About Sex Education On Sexual Harassment Of Adolescents At Junior High School 2 City Of Kediri - Tety Ripursari; Nita Dwi Astikasari; Linosafance (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2026)
Lack of knowledge of adolescents about sex education so that adolescents ignore and consider sexual harassment trivial. Not a few victims of sexual harassment experience prolonged trauma such as disturbed adolescent psychology, feeling ashamed, not confident, reluctant to participate in social activities at school and in the community, even the desire or attempted suicide. The purpose of this study was to determine the influence of adolescents' knowledge about sex education on sexual harassment of adolescents at Junior High School 2 City Of Kediri. The design of this study is a correlational study with a cross-sectional approach. Respondents were taken using proportional random sampling technique. The population was 65 people with a sample of 56 people. The statistical test used chi square. The results of the study showed that knowledge about sex education in adolescents was known by almost all respondents as many as 46 (82.1%) in the good category. Sexual harassment in adolescents was known by almost all respondents as many as 53 (94.6%) in the category of no sexual harassment. The results of the data analysis show that the level of significance is 0.000 <α = 0.05 so that H0 is rejected and H1 is accepted, thus there is an influence of adolescents' knowledge about sex education on sexual harassment of adolescents. The better the knowledge of adolescents about sex education, the more adolescents will avoid sexual harassment. Health workers, teachers and parents will always provide information to adolescents so as to increase their knowledge about sex education.